The Effect of Using E-Wallet on Attitudes and Lifestyle - Anggi Puspita Dewi; Ainur Rochmaniah (Universitas Muhammadiyah Sidoarjo, 2023)
This type of research is quantitative with statistical techniques to test the variables of Use (X), Attitude (Y1), and Lifestyle (Y2). The location of this research is in Sidoarjo district. The population is the people of Sidoarjo district who use e-wallet aged 17 and over, with a sample of 185 respondents who were taken using the Roscoe formula. While the sampling technique with proportional random sampling. Data collection is done by distributing questionnaires widely. Data were analyzed by simple linear regression using SPSS 16.0. The results of this study there is no strong influence of attitudes towards the use of e-wallet in the people of Sidoarjo district, meaning that there is no influence of attitudes and lifestyle on the use of e-wallet in the people of Sidoarjo district. Contribution of usage is 0.9% to attitude and 0.10% to lifestyle, while the remaining 90.1% and 90% are influenced by other unknown variables. The conclusion of this study is that the hypothesis accepted by H1 is that there is no effect of usage on the attitudes of the people of Sidoarjo district who use e-wallet, and H2 there is no effect of usage on the lifestyle of the people of Sidoarjo district who use e-wallet.